An application of gravity model in education tourism: a case of public higher education institutions in Malaysia / Fadli Fizari Abu Hassan Asari and Asma' Rashidah Idris - Abu Hassan Asari, Fadli Fizari; Idris, Asma' Rashidah (Research Management Institute (RMI), 2010)
The tourism industry is currently Malaysian third most important industry in terms of foreign exchange earnings after the manufacturing and palm oil sectors. However, conventional tourism activity is vulnerable to current shocks e.g. Bird Flu, H1N1 pandemic and terrorist activities. Therefore alternative tourism activity such as education tourism (edu-tourism) has become one of the solutions. The objective of the study is to model international student enrolments using the Gravity Model whereby Malaysian public higher education institutions is the reference point. Results from panel data analysis using GLS-Two Way Estimation indicate that distance is the most elastic variable in determining the education tourism demand. The higher the distance, the lower enrolment it will be. Meanwhile, education tourism demand is positively related with Malaysian export. In addition, more enrolled students come from countries which have socio-economic agreement with Malaysia. Appropriate actions have been proposed, to place Malaysia as one of the major exporters in education tourism industry, parallel with its vision to become an international center of excellence for education beyond year 2020.